Constructing a sustainable learning organization: Marks and Spencer's first Plan A learning store. Issue 2 (8th April 2014) - P. Wilson, John; Beard, Colin
Abstract : Purpose: – Marks and Spencer's Plan A environmental strategy is an ambitious one which addresses economic, social and environmental considerations. As part of this process it recently used a sustainable learning store strategy to develop, capture and disseminate learning before, during and after construction so that learning could be transferred to future projects. Significantly, the strategy did not draw on "traditional" learning organisation concepts; instead it developed its own bottom-up approach to identify the important areas for learning. The practices developed for the learning store were then evaluated against a learning organisation blueprint. Design/methodology/approach: – A literature review of learning organisations in construction was complemented by a case study of the prototype Marks and Spencer learning store. The strategies adopted by the company were assessed against Pedler et al .'s blueprint for a learning company. Findings: – The systematic learning store strategy developed by Marks and Spencer matched the 11 main criteria described by Pedler et al. 's learning company blueprint and also included managing and leading. The strategies adopted by M&S have the potential to be adopted by other organisations seeking to become environmentally sustainable learning organisations. Research limitations/implications: – This case study was undertaken from the perspective of one retail organisation and did not directly evaluate the other stakeholders. It was also largely cross-sectional in nature and describes the learning which occurred but not its application to any subsequent downstream projects. Its applicability to other industries and organisations therefore needs to be investigated further. Practical implications: – The strategies used during the development of the Marks and Spencer's learning store have the potential to be adopted by other retail, construction and organisations from other sectors and have significant benefits to the environment. Originality/value: – Little has been written about the practical application of sustainability approaches for learning organisations. The scale and scope of the Plan A strategy would not appear to have been achieved by other organisations.